A feed composition comprising napier silage - Mat Yusof, Afzan; Mohd Amin, Mohd Hishammfariz; Md Isa, Muhammad Lokman (2019)
The present invention relates to a feed composition for a ruminant and more particularly to a feed composition for increasing milk and meat production in a ruminant.